2019
DOI: 10.21203/rs.2.9133/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-analysis of Corneal Biomechanical Effects after SMILE and FS-LASIK

Abstract: Background: To evaluate and compare corneal biomechanics after treatment of myopia using small-incision lenticule extraction (SMILE) and femtosecond laser-assisted in situ keratomileusis (FS-LASIK). Methods: We performed a meta-analysis and searched for reports concerning corneal biomechanics after SMILE and FS-LASIK using MEDLINE, EMbase, CNKI and the Cochrane Library. The analysis included corneal hysteresis (CH) and corneal resistance factor (CRF) before and 3 months after the surgery. The quality of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, the high disparity among outcomes of the clinical studies aiming to compare corneal biomechanical behavior after SMILE with that of other surgical techniques have rendered this hypothesis to be controversial. 3,7,[11][12][13][14][15][16][17][18][19][20] With analysis of stromal tissue samples, Khamar et al 13 showed early molecular changes after SMILE and LASIK. They concluded that SMILE resulted in a better wound healing response, less stromal or nerve damage, and reduced postoperative complications compared with LASIK.…”
mentioning
confidence: 99%
“…However, the high disparity among outcomes of the clinical studies aiming to compare corneal biomechanical behavior after SMILE with that of other surgical techniques have rendered this hypothesis to be controversial. 3,7,[11][12][13][14][15][16][17][18][19][20] With analysis of stromal tissue samples, Khamar et al 13 showed early molecular changes after SMILE and LASIK. They concluded that SMILE resulted in a better wound healing response, less stromal or nerve damage, and reduced postoperative complications compared with LASIK.…”
mentioning
confidence: 99%